Systematic Evaluation of Light-Activatable Biohybrids for Anti-Glioma Photodynamic Therapy - Inglut, Collin T. (J Clin Med, 2019)
Photosensitizing biomolecules (PSBM) represent a new generation of light-absorbing compounds with improved optical and physicochemical properties for biomedical applications. Despite numerous advances in lipid-, polymer-, and protein-based PSBMs, their effective use requires a fundamental understanding of how macromolecular structure influences the physicochemical and biological properties of the photosensitizer. Here, we prepared and characterized three well-defined PSBMs based on a clinically used photosensitizer, benzoporphyrin derivative (BPD). The PSBMs include 16:0 lysophosphocholine-BPD (16:0 Lyso PC-BPD), distearoyl-phosphoethanolamine-polyethylene-glycol-BPD (DSPE-PEG-BPD), and anti-EGFR cetuximab-BPD (Cet-BPD). In two glioma cell lines, DSPE-PEG-BPD exhibited the highest singlet oxygen yield but was the least phototoxic due to low cellular uptake. The 16:0 Lyso PC-BPD was most efficient in promoting cellular uptake but redirected BPD’s subcellular localization from mitochondria to lysosomes. At 24 h after incubation, proteolyzed Cet-BPD was localized to mitochondria and effectively disrupted the mitochondrial membrane potential upon light activation. Our results revealed the variable trafficking and end effects of PSBMs, providing valuable insights into methods of PSBM evaluation, as well as strategies to select PSBMs based on subcellular targets and cytotoxic mechanisms. We demonstrated that biologically informed combinations of PSBMs to target lysosomes and mitochondria, concurrently, may lead to enhanced therapeutic effects against gliomas.